2021
DOI: 10.1213/ane.0000000000005540
|View full text |Cite
|
Sign up to set email alerts
|

Propofol for Induction and Maintenance of Anesthesia in Patients With Brugada Syndrome: A Single-Center, 25-Year, Retrospective Cohort Analysis

Abstract: helped design the study, develop the protocol, get Institutional Review Board approval, analyze the results and develop the manuscript. Kea Viaene M.D.* a : * The first two authors equally contributed to the study. This author helped design the study, develop the protocol, get Institutional Review Board approval, analyze the results and develop the manuscript. Maurizio Tosi M.D. a : This author helped design the study, develop the protocol, writing methods and editing the manuscript. Hugo Carvalho M.D. a : Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…All studies were published in medical journals and were in English. These included twenty-nine case reports , nine case series (46)(47)(48)(49)(50)(51)(52)(53)(54), eleven clinical trials out of which four were randomized (55-58) and seven were non-randomized (59)(60)(61)(62)(63)(64)(65). The process of study selection has been summarized in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published in medical journals and were in English. These included twenty-nine case reports , nine case series (46)(47)(48)(49)(50)(51)(52)(53)(54), eleven clinical trials out of which four were randomized (55-58) and seven were non-randomized (59)(60)(61)(62)(63)(64)(65). The process of study selection has been summarized in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…While propofol is one of the most widely used intravenous anesthetics, there has been extensive debate regarding the safety of propofol bolus or continuous infusion in patients with Brugada syndrome because of its arrhythmogenic effects [ 6 ]. Recently, Flamée et al reported its safe use without critical arrhythmias in the operating theater or the intensive care unit [ 7 ]. In addition, they also reported that induction with propofol or etomidate did not affect ST-segment elevation [ 9 ] whereas Ciconte et al showed that propofol significantly reduced ST-segment elevation immediately after induction [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our plan can realize induction 6) At eye-opening upon emergence from anesthesia. (7) Immediately before transfer to the high care unit. B Changes in the value of ST-segment (J-point) amplitudes in lead V2 in the operating room.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, recent research could not provide evidence of the alleged arrhythmogenicity of propofol in such patients. 4 , 5 Currently, a prospective study for investigating those effects is ongoing (EudraCT Register: 2019-004750-28)…”
mentioning
confidence: 99%